Characterisation of improved foam aeration and rheological properties of ultrasonically treated whey protein suspension - Tan, Mei Ching; Chin, Nyuk Ling; Yusof, Yus Aniza; Taip, Farah Saleena; Abdullah, Jaafar (Elsevier, 2015)
Suspensions of 10, 15 and 20% (w/v) whey protein concentrate (WPC) were treated with 20 kHz ultrasound for 5, 15 and 25 min at an amplitude of 20, 40 or 60%. The treated suspensions were whipped into foam and the aeration and rheological properties were investigated. With increasing ultrasound amplitude and treatment time, whey protein foam at 15% concentration produced the highest foaming capacity, while foam stability, storage modulus, loss modulus, consistency index and viscosity of foam increased with protein concentration. Foam viscosity correlated with foam stability with R2 = 0.7425 and significant at P < 0.001.